Effect of exhaust gas recirculation to performance and emissions of diesel engine - Mustaqim, Mohamad (2010)
Direct injection (DI) diesel engine is well design today as a main power train solution for trucks and others relevant heavy duty vehicles. However, at the same time emission legislation, mainly for oxides of nitrogens (NOx) and particulate matter (PM) becomes more obvious, reducing their limit to extremely low values. One efficient method to control NOx in order to achieve the future emission limit are the rather high exhaust gas recirculation (EGR) rates accompanied by increased boost pressure to avoid the negative impact on soot emissions. EGR is one of the most effective means of reducing NOx emissions from compression ignition (CI) engines and is widely used in order to meet the emission standards. In the present work, experimental investigation has been carried out to make an analysis the NOx reduction characteristics and the effect to the engine performance by using exhaust gas recirculation between two different fueled engine using biodiesel (palm oil methyl ester B5) and light diesel. This experiment was carried out using a four-cylinder DI diesel engine Mitsubishi 4D68. The purpose of this experiment was conducted is to know the effect of EGR on diesel engine performance and the quantity of NOx emissions in diesel engine’s exhaust. The performance of the diesel engine and the quantity of NOx emissions in exhaust gas with using EGR in this experiment will be compared with the performance of the engine and the quantity of NOx emissions in the exhaust gas which not using EGR during the experiment. The results obtained by experiments showing that the EGR has caused the engine performance decreased as compared with no use of EGR. EGR is the best solution for reduced the production of NOx in the exhaust.